Analyzing and Forecasting International Tourist Arrivals in Nepal: Trends, Patterns, and Future Prospects - Pradhan, Bijay Lal; Koirala, Prabesh (International Journal of Operational Research/Nepal, 2024)
This paper aims to analyze and forecast international tourist arrivals in Nepal, a country known for its rich cultural heritage and breathtaking natural landscapes. Using time series analysis and ARIMA modeling, the study investigates the data on tourist arrivals, highlighting the significant impact of the COVID-19 pandemic on travel trends. Descriptive statistics were used to examine tourist demographics including gender, age groups, and the purpose of visit, revealing seasonal trends that influence arrival patterns. The findings indicate that international tourism plays a vital role in Nepal’s economy, while the pandemic has led to unprecedented decline in arrivals. The study offers valuable insights for policymakers and stakeholders in the tourism sector, emphasizing the need for sustainable tourism development and investment in infrastructure to recover and enhance the country’s tourism potential. By providing forecasts of future tourist arrivals, this research serves as a critical tool for strategic planning in the post-pandemic landscape.